2006
DOI: 10.1124/mol.105.020107
|View full text |Cite
|
Sign up to set email alerts
|

Liver Deformation in Ahr-Null Mice: Evidence for Aberrant Hepatic Perfusion In Early Development

Abstract: Mice harboring mutations in the Ahr locus display a patent ductus venosus and smaller livers throughout life. We tested the hypothesis that these hepatic aberrations are secondary to a developmental defect in hepatovascular blood flow by performing a detailed analysis of hepatic development in wild-type and Ahr Ϫ/Ϫ mice. This study revealed necrotic lesions in the peripheries of Ahr Ϫ/Ϫ fetal livers as early as embryonic day 15.5, with an increasing incidence up to postnatal day 1 and resolution by 2 weeks pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 26 publications
0
48
1
Order By: Relevance
“…Although it has been established that dioxin-produced hepatotoxicity occurs via an AhR-governed mechanism, [3][4][5] knocking-out of AhR results in atrophy and dysfunction of the liver even in the absence of dioxin treatment. [3][4][5]37) Thus, it is likely that the endogenous activation of AhR is important for the maintenance of hepatic function and morphology. [3][4][5]37) This study suggests that restricting food intake alters the levels of tryptophan metabolites including a reduction in urinary excretion of L-kynurenine which is a candidate endogenous AhR ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been established that dioxin-produced hepatotoxicity occurs via an AhR-governed mechanism, [3][4][5] knocking-out of AhR results in atrophy and dysfunction of the liver even in the absence of dioxin treatment. [3][4][5]37) Thus, it is likely that the endogenous activation of AhR is important for the maintenance of hepatic function and morphology. [3][4][5]37) This study suggests that restricting food intake alters the levels of tryptophan metabolites including a reduction in urinary excretion of L-kynurenine which is a candidate endogenous AhR ligand.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]37) Thus, it is likely that the endogenous activation of AhR is important for the maintenance of hepatic function and morphology. [3][4][5]37) This study suggests that restricting food intake alters the levels of tryptophan metabolites including a reduction in urinary excretion of L-kynurenine which is a candidate endogenous AhR ligand. 38) Such attenuation in AhR ligand possibly produces a rise in abnormal morphology and liver function.…”
Section: Discussionmentioning
confidence: 99%
“…ahr (Ϫ/Ϫ) mice, although viable, exhibit multiple organ dysfunction (Schmidt et al, 1996), abnormal vasculature (Harstad et al, 2006), compromised immune system (Rodríguez-Sosa et al, 2005), and reduced life span and limited fertility (Abbott et al, 1999). In line with these phenotypic abnormalities, the repertoire of AhR-regulated genes, the "AhR battery" now incorporates targets not directly involved in detoxification.…”
mentioning
confidence: 95%
“…In the immune system, AhR was involved in regulating the antigen responses in Th17 cells, dendritic cells, and other adaptive immune cells (Esser, 2009;Esser et al, 2009;Tian et al, 2015). In addition, smaller liver size and hepatic deformation were observed in adult AhR KO mice (Harstad et al, 2006), and the animals were more likely to develop liver tumors after exposure to diethylnitrosamine (Fan et al, 2010). Besides, a recent investigation demonstrated that AhR KO mice had a higher risk of developing bladder stones (Butler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%